Nasikh-Mansukh Dalam Al-Qur’an: (Diskursus Penentuan Jumlah Ayat Yang Dinasakh) - Khairul Bahri Nasution (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2022)
Nasakh besides being a method, it is also part of the conditions for ijtihad for a mujtahid. Nasakh in its definition is interpreted in various ways by scholars, among them there are those who interpret it with al-izalah wal ibthal (removal and cancellation), some with the meaning of an-naql wat-tahwil (transfer and transfer). The controversy over the textual theory does not stop at this definition, it also widens the controversy to the stage of groups who accept and reject the text, even among the recipients of the text there are also polemics, such as their polemic about which verses are alleged to have been translated. In determining the number of verses to be assigned, scholars vary, some mention 214 verses, some say 134 verses, some say 66 verses, up to 5 verses. From their differences, it was found that only two verses were agreed upon by their texts, namely: 1) Q.S. al-Mujadilah: 12, 2) Q.S. al-Muzzammil : 1-3.